Microsatellite Instability And Loss Of Heterozygosity In Oral Squamous Cell Carcinoma In A Malaysian Population - Jusoh, Julia Ashaliza Mat (2012)
Loss of heterozygosity (LOH) and microsatellite instability (MSI) have been documented as important events of oral squamous cell carcinoma (OSCC). Five microsatellite markers D3S192, D3S966, D3S647, D3S1228 and D3S659 were selected on chromosome 3p because of high frequency of alterations reported in head and neck squamous cell carcinoma and the involvement of VHL (von Hippel Lindau) at 3p25-26 and the FHIT (fragile histidine triad) at 3p14.2 genes proven in many tumor types. A total of 50 archival tissue samples of OSCC and corresponding normal samples were analyzed for LOH and MSI status. The overall LOH for the markers selected on 3p was 56 out of 189 informative cases (29.6%).